Proceedings of the International Conference on Science and Education and Technology (ISET 2019) 2020
DOI: 10.2991/assehr.k.200620.039
|View full text |Cite
|
Sign up to set email alerts
|

Education of Environmental Awareness Based on Larung-Sesaji Ritual in Coastal Community of Bluru Village, Sidoarjo Sub-District, Sidoarjo District

Abstract: Environmental awareness Education aims to print a wise generation against the surrounding environment, issues about the environment, both nationally and internationally never depart from the attention of World society. The impacts of human behavior or natural disasters caused by environmental education need to be implanted early. Learning activities related to environmental education can be done directly and indirectly, directly through school education while indirectly through traditions that exist in the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Through symbols such as Parukuyan, Puncak Manik, and Sesajen, the participants of the ritual are directed to appreciate nature, diversity, and local culture. Previous research has shown that symbolism in cultural rituals can serve as an effective means of education and understanding of environmental values and conservation alam (Ardoin & Heimlich, 2021;Niswatin, Wasino, Suyahmo, & Arsal, 2020;Swan, 1983). In the context of Ruwatan Leuweung Babakti Mandala Manglayang, this symbolism becomes a vital tool to raise awareness among participants about the importance of maintaining harmony with nature, preserving local cultural values, and addressing environmental issues wisely.…”
Section: Symbolism In Ritual For Environmental Conservationmentioning
confidence: 99%
“…Through symbols such as Parukuyan, Puncak Manik, and Sesajen, the participants of the ritual are directed to appreciate nature, diversity, and local culture. Previous research has shown that symbolism in cultural rituals can serve as an effective means of education and understanding of environmental values and conservation alam (Ardoin & Heimlich, 2021;Niswatin, Wasino, Suyahmo, & Arsal, 2020;Swan, 1983). In the context of Ruwatan Leuweung Babakti Mandala Manglayang, this symbolism becomes a vital tool to raise awareness among participants about the importance of maintaining harmony with nature, preserving local cultural values, and addressing environmental issues wisely.…”
Section: Symbolism In Ritual For Environmental Conservationmentioning
confidence: 99%
“…This especially is when learning social studies at the junior high school level around Boja Village. Learning by applying local wisdom can guide environmental-based education in the community (Niswatin et al, 2020). Social studies education integrates education and culture, namely all ideas, behaviors, and human creations developed through a learning process (Ridwan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Khanduri laot has noble values that are beneficial for the sustainability of the life of fishing communities and the development of coastal areas. As indigenous knowledge, the khanduri laot plays a role in shaping the understanding of the fishing community about the representation, relations, and identity of environmental conservation, social, cultural (Wasino et al, 2020), economy and ecology (Niswatin et al, 2020). Quality values in khanduri laot are taken from existing community wisdom and other local resources and a sense of creativity.…”
Section: Introductionmentioning
confidence: 99%